Relationship between Islamic concept and ethical behaviour akhlak) of being in love among youth - Syaidatun Nazirah Abu Zahrin; Fazilah Idris; Khairul Anwar Mastor; Aminudin Basir@Ahmad; Rozmi Ismail; Hanisah Osman (Penerbit Universiti Kebangsaan Malaysia, 2017)
The word love is synonymous with values of goodness. Romantic relationship needs guidance from religious knowledge in order to sustain an ethical love relationship. This is to avoid involvement in social illness. The impact of being unethical in loving behaviour includes increasing number of adultery and baby dumping cases. The aim of this study is to determine the relationship between Muslim youth understanding, attitude and practice on the Concept of Love (COL) in Islam with values in Ethical Love Behaviour (ELB). The study was conducted among students at three types of higher education institutions in Malaysia which include public, private and the public Islamic universities with a total of 599 respondents. The age of the respondents are from 18 to 23 years old (mean=19.5). Respondents were asked to complete Likert type and self-administered questionnaire assessing respondents’ understanding and attitude towards dimensions of love and values in ELB. The psychological measurement tools in this study were developed by the researchers and named as the Instrument of Love in Islam (ICDI) and Ethics of Love (IAP). Findings show that understanding and attitude towards love in Islam is high; however, the practical aspect is moderate. The COL in Islam has a significant relationship with values in ELB. The findings of this study highlight the contributions of understanding and possessing positive attitude towards the COL in sustaining youth’s meaningful participation in values of ELB. The implication of this study suggests that understanding and appreciation of love is particularly relevant to youth in order to address problems of wrongful behaviours that result from misunderstanding of the concept of love.